FRUITS AND VEGETABLES MARKET HALL LOCATION SELECTION BY USING INTERVAL-VALUED TRAPEZOIDAL FUZZY GREY RELATIONAL ANALYSIS: AN APPLICATION FOR ISTANBUL - Bilisik, Ozge Nalan; Tuzkaya, Umut Rifat; Baracli, Hayri; Tanyas, Mehmet (UNIV CINCINNATI INDUSTRIAL ENGINEERING, 2019)
In urban areas, effectively delivering the necessary products for people to survive to the desired points has vital importance. Selecting the locations of urban distribution centers correctly, which have an essential role in distribution networks, will satisfy determining the number of vehicles, minimizing the traffic congestion by determining the routes of vehicles correctly and thus decreasing the environmental effects like noise and emission. In this study, location selection problem for fresh fruits and vegetables market hall (F&VMH) which is an important urban distribution center type that fulfills the food requirements of city residents is examined. The interval-valued trapezoidal fuzzy grey relational analysis (GRA) method is used to solve this problem because, it is suitable to deal with poor, incomplete, and uncertain information. When the results are analyzed, it is seen that F&VMHs have to be located in the district which is closer to producers and which has the lower construction and land costs.
Keywords: distribution; decision making; fruits and vegetables market halls; location selection; INTERNATIONAL DISTRIBUTION CENTER; DECISION-MAKING; HUB LOCATION; LOGISTICS; AHP; MODEL; WHOLESALE; FRAMEWORK; PRODUCTS; QUALITY; Engineering